Case reportGastric gastrointestinal stromal tumor with incomplete duplication cyst – a case with possibility of neoplasia in fetal-period malformed tissues - Lewitowicz, Piotr; Matykiewicz, Jaroslaw; Koziel, Dorota; Gluszek, Stanislaw Z.; Sosnowski, Zbigniew; Horecka-Lewitowicz, Agata; Nasierowska-Guttmejer, Anna (Polish Journal of Pathology, 2015)
The coincidence of GIST and other gastric malignancies are documented well but arising GIST from congenital anomalies is still rarity in literature. To date, only a few papers have been concerned on the possibility of arising neoplasms from duplication cyst of gastrointestinal tract. There, are dominating usual cancers, neuroendocrine cancers or lymphomas but GIST has been noted only once. Here, we report a case of 73 years old female-patient with typical gastric stromal tumor comprised centrally locked an incomplete duplication cyst.